Estágio supervisionado obrigatório Laminite equina: relato de caso - Maia Terceiro, Vicente Diogo (Universidade Federal Rural do Semi-Árido, 2021)
The mandatory internship was carried out through monitoring the routine of veterinary care and supervision of the veterinarian Dra. Taiany de Sousa Silva, in agreement with the Federal Rural University of the Semi-Árido (UFERSA), campus Mossoró-RN. The objective was to monitor the routine of a veterinarian, improving in this internship period the theoretical- practical knowledge acquired during graduation and, finally, preparing a case report of equine laminitis. The patient, an adult mare, after clinical examination and with an radiography, characteristics related to laminitis where observed and confirmed with an observation of a degree 1 phalanx rotation, characteristic of chronic laminitis, and the animal underwenttreatment consisting of the application of cryotherapy, associated with the use of medication and maintenance of the hooves, thus allowing the recovery of the animal. Laminitis is an important pathology for equine culture and needs to be well studied by the veterinarian so thathe can recognize the signs and apply the necessary treatment, a goal that was achieved in this mandatory curricular internship.
Keywords: Crioterapia; Equinocultura; Médico veterinário; Laminite crônica; CIENCIAS AGRARIAS::MEDICINA VETERINARIA